Sulu Çözeltiden Alizarin Sarısı Boyarmaddesinin Nanoadsorbent (MNPs-G1-Mu) Vasıtasıyla Adsorpsiyon Özelliklerinin Belirlenmesi - Ekinci, Selma; İlter, Zülfiye (Batman Üniversitesi, 2021)
Bu çalışmada Alizarin Sarısı boyarmaddesinin sulu çözeltiden adsorpsiyon yöntemiyle uzaklaştırılması amaçlanmıştır. Adsorpsiyon işleminde adsorbent olarak bir nano materyal olan MNPs-G1-Mu kullanılmıştır. Temas süresi, pH, başlangıç boyarmadde konsantrasyonu ve adsorbent miktarının adsorpsiyona etkileri incelenmiş olup, bu adsorpsiyon işlemi için uygun koşullar belirlenmiştir. Daha sonra adsorpsiyon kinetiğinin araştırılması için kinetik veriler kinetik denklemlerde (Pseudo Birinci Derece Kinetik Denklemi ve Pseudo İkinci Derece Kinetik Denklemi) değerlendirilmiştir. Adsorpsiyonun her iki kinetik denkleme de uyduğu belirlenmiştir. Son olarak, MNPs-G1-Mu ile Alizarin Sarısı boyarmaddesinin adsorpsiyonuna ait izoterm çalışması yapılarak, deneysel verilerin Langmuir ve Freundlich adsorpsiyon izotermlerine uygunluk gösterdiği belirlenmiştir. Bu izotermlerden faydalanılarak Langmuir sabiti (qm) ve b ile Freundlich sabitleri k ve n hesaplanmıştır. Sonuç olarak, MNPs-G1-Mu adsorbentinin Alizarin Sarısı boyarmaddesini %90,43 verimle adsorpladığı belirlenmiştir.

In this study, it was aimed to remove the Alizarin Yellow dyestuff from the aqueous solution by adsorption method. MNPs-G1-Mu (iron oxide nanoparticles modified with Pamam dendrimer and murexide), a nano material, was used as an adsorbent in the adsorption process. The influences of equilibrium contact time, pH, initial dyestuff concentration and the amount of adsorbent on the adsorption were investigated, and suitable conditions were determined for this adsorption process. Then, the kinetical data were evaluated to kinetic equations (Pseudo First Order Kinetic Equation and Pseudo Second Order Kinetic Equation) to investigate the adsorption’s kinetical behaviour. It was determined that the adsorption process was fitted to both kinetic equations. After that, the isotherm study of the adsorption of Alizarin Yellow on MNPs-G1-Mu dyestuff was performed and it was concluded that the experimental data were suitable for both Langmuir and Freundlich adsorption isotherms. By using these isotherms’ linear equations, Langmuir constants qm and b were calculated as 15,384 mg g-1 and 0,105 respectively; Freundlich constants k and n were calculated as 3,589 and 3,115 respectively. As a result, it was determined that MNPs-G1-Mu adsorbed the Alizarin Yellow dyesuff with % 90,43 efficiency.
Determination of The Adsorption Properties of Alizarin Yellow Dyestuff from Aqueous Solution by Nano Adsorbent